2021
DOI: 10.1111/ajr.12787
|View full text |Cite
|
Sign up to set email alerts
|

Starting from scratch: Developing and sustaining a rural research team lessons from a nutrition and dietetics case study

Abstract: Objective To describe the development of and key factors for sustaining a rural‐based research team focussed on nutrition and dietetics. Design A longitudinal embedded case study approach with data sourced from publicly available records and observations. Case study sub‐units were developed into 3 phases with analysis using theoretical propositions and pattern matching. Quantitative data were descriptively analysed. Setting University of Newcastle Department of Rural Health across 4 rural sites. Participants P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…They highlight the importance of quality child support for rural health workers. The case study by Brown et al 20 reflects on the experiences of building a sustainable dietetic research team and the importance of continued professional development. They note the importance of gaining a critical mass of same discipline academics that can support each other to improve rural research in that field, and the importance of having multidisciplinary and metropolitan engagement.…”
Section: The Grand Challengesmentioning
confidence: 99%
“…They highlight the importance of quality child support for rural health workers. The case study by Brown et al 20 reflects on the experiences of building a sustainable dietetic research team and the importance of continued professional development. They note the importance of gaining a critical mass of same discipline academics that can support each other to improve rural research in that field, and the importance of having multidisciplinary and metropolitan engagement.…”
Section: The Grand Challengesmentioning
confidence: 99%
“…Therefore, they have comparatively fewer opportunities to lead and participate in research. 5,7,8,14,15 Indeed, it has been identified that strategies to develop a safe, high-quality and sustainable rural and regional health system in Victoria must encompass enhanced research infrastructure in these areas. 20 For example, establishing research positions and partnerships Effective RCB initiatives encompass a range of integrated strategies targeted at the policy or systems, organisational, team and individual level.…”
Section: Introductionmentioning
confidence: 99%
“…7 Promoting health service-led research in rural areas is critical to ensuring relevant evidence is generated to improve service delivery and, in turn, the health outcomes of people living in these communities. [7][8][9]13,14 Rural health services and health professionals, however, have less access to research infrastructure, research capacity building (RCB) initiatives and research funding than their metropolitan counterparts. Therefore, they have comparatively fewer opportunities to lead and participate in research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations